Pelatihan Pembuatan Video Pembelajaran Bahasa Inggris Pada Guru-Guru SD Mudimat Mataram NTB - Humaira Humaira; Siti Lamusiah; Fauzi Bafadal; Isnaini Isnaini; Muslimin Muslimin (El-Khidmat, 2024)
Since the pandemic hit various parts of the world, almost all learning processes have been conducted online. This requires teachers to be technologically literate and up-to-date with information, including Android applications. The same applies to English teachers, who are highly encouraged to keep up with technological and informational developments to follow the latest, fun, and engaging teaching models. Therefore, this community service is carried out to assist teachers in creating and producing English learning videos using easy and effective applications. Teachers can directly use their Smartphone as tools and media for video production, making it practical. The community service activity was conducted at SD Muhammadiyah Mataram with three teachers as respondents. This activity also involved students as companions or tutors who explained and guided the steps of making videos, including editing, layout, and production. The edited videos would then be shared on each teacher's YouTube link. Teachers just need to send the link to their students.